The Influence of Job Stress on the Intention to Change Jobs Through Employee Engagement (A Study on Millennial Generation Employees) - Anisa Pujianti Bachtiar; Rais Dera Pua Rawi; Susetyowati Sofia; Agilistya Rahayu (www.amertainstitute.com, 2024)
This study investigates the impact of work stress on turnover intention, with employee engagement as a mediating variable. Employing a quantitative approach, the research utilizes a structured questionnaire for data collection. The population comprises 120 millennial employees, and the study adopts a non-probability sampling technique, specifically purposive sampling, to select respondents. Data analysis is conducted using Smart PLS 4.0, a robust statistical tool for examining complex relationships between variables. The findings reveal a significant relationship between work stress and employee engagement, indicating that increased work stress levels directly affect employee engagement. However, the analysis shows that employee engagement does not significantly influence turnover intention, suggesting that engaged employees may still consider leaving their organizations under certain conditions. Furthermore, there is a direct and significant relationship between work stress and turnover intention, underscoring the critical role of stress in driving employees' decisions to exit their workplace. The mediation test indicates that employee engagement does not effectively mediate the relationship between work stress and turnover intention. This implies that while engagement is influenced by stress, it does not sufficiently buffer the negative impact of stress on employees' intention to leave. These findings provide valuable insights for organizations aiming to mitigate turnover by addressing workplace stressors effectively.